Gonadal Maturation and Reproductive Timing in Batch Spawning Tropical Cypriniform Fishes Lobocheilos ovalis, Rasbora argyrotaenia and Tor tambra - Rafhiah Kahar; Norhayati Ahmad; Takaomi Arai (Aquaculture, Fish and Fisheries, 2024)
ABSTRACT This study is the first to investigate the reproductive traits of Lobocheilos ovalis (n = 621), Rasbora argyrotaenia (n = 507) and Tor tambra (n = 138) through detailed gonad histology. We collected L. ovalis and R. argyrotaenia specimens from September 2017 to August 2019 and T. tambra from July 2018 to August 2019 from tropical rainforest streams in Ulu Temburong National Park Brunei Darussalam. In all three species, females were larger and attained sexual maturation at larger sizes than males. Gonad histology categorized five reproductive phases in the ovarian and testicular maturation cycle comprising the immature, developing, spawning capable, regressing and regenerating phases. Ovarian histological markers of the reproductive phases included increasing oocyte diameters and gradual changes in cytoplasmic and nuclear features. In testes, decreasing nuclear diameters, darkening nuclear stains and germinal epithelium continuity were significant histological markers. Monthly frequencies of reproductive phases showed that L. ovalis and R. argyrotaenia were reproductively active throughout the year, whereas T. tambra exhibited protracted spawning over several months. Gonad histology also revealed asynchronous ovarian development and batch spawning, facilitating these species’ year‐round and protracted spawning. This reproductive strategy may be an adaptation for these species to increase the survival of offspring in hillstream habitats where flash floods are common. The present study significantly fills existing knowledge gaps in Southeast Asian cypriniform fishes, providing a reference point for gonad histology to elucidate the reproductive traits and ecology, particularly for the Lobocheilos, Rasbora and Tor genera. Importantly, it provides practical insights for the conservation and management of the wild populations of these species.